The cooking palm oil price determinants after palm oil-free labeling - Hary S. Sundoro; Grace Putlia (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2021)
This study aims to predict the effect of CPO (crude palm oil) prices or government policies such as BI 7days and CPO export taxes on palm cooking palm oil prices in Indonesia during the Palm Oil-Free labeling period. To address this research issue, this study uses the VECM method by implementing the Impulse Response Function (IRF) and variance decomposition approaches to analyze the research data. Further, the research period starts from January 2017 to April 2020. The study results show that CPO prices affect palm cooking palm oil prices positively. On the contrary, the government policies such as BI 7days and CPO export taxes negatively affect cooking palm oil prices during the Palm Oil-Free labeling period. Further, this study also informs that of all the determinant variables, CPO prices have the greatest response to the fluctuations in cooking palm oil prices. Thus, this study suggests the government to constrain raw material or CPO prices to reduce palm cooking palm oil prices in the domestic market.